Main Characteristic Of User Requirements For The Transformation Of Existing Bus Terminal In Northern Region Of Malaysia - Madsah, Norhidayu (2017)
The states of North Malaysia are now growing rapidly in line with the increasing demand for public transport. However, public facilities available at the bus terminals in the states of North Malaysia are still in poor condition and still have no friendly user features. Therefore, this study is conducted to evaluate the most sensible facilities to be provided at each bus terminal by conducting a comparative study based on user perspectives and needs affecting current user results at bus terminals in Perak, Kedah and Penang. In order to achieve the objectives of the study, a questionnaire survey was distributed to 380 public users at the terminal area. Further, computational frequency and critical calculations were calculated to determine the position for the convenient factor based on user preferences. The findings showed that Hentian Raya Parit Buntar is in the top list with its existing features in a great condition. Meanwhile, the Hentian Shahab Perdana is in the last list with their existing facilities in a bad condition. Further research found that the top priority of facilities to cater the needs by consumers are the sectoral services required at terminals such as 1 Malaysia Clinic, Pos Malaysia Post Office, Police Station and SPAD Office. The second highest list is the need to improve the parking area, where a multi-storey car park should be built to meet parking demands and providing near entrance car parking for disables people. The third highest list is a friendly facility for the disabled people. Special lane with guidance should be prepared for this group. The facilities that have disable user-friendly features must be ensured to be available in lifts and toilets. Besides that, texture of the floor for the elderly and the slope paths for those who using the wheelchairs must also be ensured to always be in a safe condition. In conclusion, this study suggests the implementation of transformation and improvements on the existing public facilities at terminal buses in terms of terminal managements and local authorities of Perak, Kedah and Penang.